Cover Image. Issue 3 (22nd July 2020) - Lachaux, Marianne; Soulié, Matthieu; Hamzaoui, Mouad; Bailly, Anaëlle; Nicol, Lionel; Rémy‐Jouet, Isabelle; Renet, Sylvanie; Vendeville, Cathy; Gluais‐Dagorn, Pascale; Hallakou‐Bozec, Sophie; Monteil, Christelle; Richard, Vincent; et al.
Abstract : Cover caption The cover image is based on the Original Article " Short‐ And Long‐Term Administration of Imeglimin Counters Cardiorenal Dysfunction in a Rat Model of Metabolic Syndrome by Marianne Lachaux et al., https://doi.org/10.1002/edm2.128 ".